Pengaruh Tenur Kap Audit Delay Ukuran Kap Dan Ukuran Perusahaan Klien Terhadap Kualitas Audit Dengan Audit Fee Sebagai Variabel Moderasi (Studi Empiris pada Sektor Keuangan Subsektor Perbankan yang Terdaftar di Bursa Efek Indonesia tahun 2018 - 2020) - Alexander Satria; Jovanna Jovanna; Michael Alvin; Wilsa Road Betterment Sitepu (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
This study examines the effect of KAP tenure, audit delay, KAP size and client firm size on audit quality with audit fee as a moderating variable. The banking sub-sector company has a population of 45 banks, selecting the sample by purposive sampling, the remaining 36 valid banks are used as research samples. The data source uses secondary sources obtained from audited financial statements of the bank sub-sector for the 2018-2020 period. Processing using logistic regression analysis and MRA. The results of the processing, namely KAP tenure, audit delay and individual KAP size are assumed not to affect audit quality, but only the size of the client company has a significant effect on audit quality. In addition, the audit fee cannot act as a moderator between the variables of KAP tenure, audit delay, KAP size and client firm size on audit quality.